The views of victim/survivors of sexual violence about perpetrator post-release measures - Richards, Kelly (Criminal justice studies, 2023)
People convicted of sexual offences are increasingly subject to a range of post-prison measures designed to reduce their risk of reoffending, including civil commitment, public offender registers, electronic monitoring and Circles of Support and Accountability. The views of a range of stakeholders, including policy-makers, legislators, and perpetrators themselves, have previously been documented about these measures. However, very little research has sought to document victim/survivors’ views, despite victim/survivors having a vested interest in the efficacy of such measures. This study began to address this gap by investigating the views of victim/survivors of sexual violence about post-release measures for perpetrators. To do this, the research reported here involved conducting semi-structured qualitative interviews with 33 victim/survivors of sexual violence. The research found that victim/survivors favor post-release measures that reflect either purely consequentialist or a hybrid of consequentialist and deontological motivations. The study’s findings will be of relevance to legislators and policy-makers, who increasingly see value in incorporating the views of victim/survivors into the development of measures designed to respond to perpetrators of sexual violence.